1999
DOI: 10.1107/s0909049599009747
|View full text |Cite
|
Sign up to set email alerts
|

Imaging by parabolic refractive lenses in the hard X-ray range

Abstract: The manufacture and properties of compound refractive lenses (CRLs) for hard X-rays with parabolic pro®le are described. These novel lenses can be used up to $60 keV. A typical focal length is 1 m. They have a geometrical aperture of 1 mm and are best adapted to undulator beams at synchrotron radiation sources. The transmission ranges from a few % in aluminium CRLs up to about 30% expected in beryllium CRLs. The gain (ratio of the intensity in the focal spot relative to the intensity behind a pinhole of equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
321
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 395 publications
(341 citation statements)
references
References 34 publications
3
321
1
Order By: Relevance
“…There are no principal preferences of using either curved mirrors or compound-refractive lenses (CRL) for this purpose. However, in practical terms, mirrors maybe a preferable choise ensuring higher efficiency, because photoabsorption of 9.1-keV and especially of 4.5-keV photons is substantial in the CRLs [19,20].…”
Section: Appendix C: Focusing and Collimating Opticsmentioning
confidence: 99%
“…There are no principal preferences of using either curved mirrors or compound-refractive lenses (CRL) for this purpose. However, in practical terms, mirrors maybe a preferable choise ensuring higher efficiency, because photoabsorption of 9.1-keV and especially of 4.5-keV photons is substantial in the CRLs [19,20].…”
Section: Appendix C: Focusing and Collimating Opticsmentioning
confidence: 99%
“…It can be shown that the CRL focal length, f / E 2 , where E is the photon energy. 13 Consider E 0 as the reference energy at which the microscope is in focus. Photons with energy E 6 ¼ E 0 will produce defocused and scaled variants of the in-focus image.…”
mentioning
confidence: 99%
“…However, the CRLs employed here are not long enough to make a significant deviation from the thin lens approximation. Therefore, a more comprehensive treatment, accounting also for lens lengths, 13,[15][16][17][18] has been omitted from Eqs. (2)- (5) but can be found as supplementary material.…”
mentioning
confidence: 99%
“…A recent article [3] summarizes the accomplishments of a most active group in this field. Their lenses are parabolas because these lack spherical aberration, and the lens curvature decouples from the aperture [4]: N lenslets with a radius of curvature R 0 in series have a focus at f = R 0 /2Nδ . Without optical equivalent is Cederstrom's multi-prism [5].…”
Section: Introductionmentioning
confidence: 99%
“…the ratio of the index of refraction decrement over the absorption coefficient. Because lithium produces the largest phase shifts per unit absorption length of all solids, we [6,7,8,9] and others [10,11] use lithium in the best available lens designs [4,5].…”
Section: Introductionmentioning
confidence: 99%